High-densitylipoprotein function in various pathological conditions - N. N. Smirnova; N. В. Kuprienko; S. А. Urazgildeeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The review considers changes in the structure and function of high-density lipoproteins (HDL), which play an important role in the pathogenesis of a number of chronic diseases that somehow stimulate the development of atherosclerosis. HDL function has been shown to be impaired in a number of genetic and acquired diseases leading to dyslipidemia and associated with increased cardiovascular risk such as familial hypercholesterolemia, obesity, metabolic syndrome, chronic kidney disease, diabetes mellitus, inflammatory and autoimmune diseases.